Labelled-the names we call our youth. - Foo, Jerry Rongjie. (2008)
Our book focuses on the impacts of labelling. It is human nature to categorize and label others who are different from us. In the case of medical labels, having the label tagged onto a person can be liberating and helpful, especially when the person is offered appropriate help which improves his or her life. However, in many cases, labels can be crippling as they often have long-lasting negative impacts on the victims.